Antibacterial composite hydrogel pulp capping agent for promoting dentin repair and preparation method thereof
By combining AgNPs with rGO with GelMA, PDA and Gap19, a composite hydrogel pulp cover agent was formed, which solved the problem of insufficient antibacterial and anti-inflammatory effects of pulp cover materials in the prior art, and effectively inhibition of bacteria and pulp Repair improves the success rate of live marrow preservation.
Patent Information
- Application Number
- CN202411453625.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
AI Technical Summary
The existing marrow capping materials cannot have both anti-inflammatory and pro-repairing effects and long-acting antibacterial effects, resulting in the failure of live marrow preservation.
Using the preparation method of composite hydrogel pulp capping agent, AgNPs-rGO/PDA/GelMA@Gap19 hydrogel is formed by mixing AgNPs with rGO and combining with GelMA, PDA and Gap19, using the antibacterial properties of AgNPs and the mechanical of GelMA. Performance and Gap19 inhibit Cx43 hemichannel activity, achieving antibacterial and prodentine restoration.
The material exhibits excellent bacterial biofilm inhibition properties, can accelerate infection wound healing, reduce inflammatory response, and promote dentin-generating differentiation of pulp cells, providing long-acting antibacterial and anti-inflammatory effects.
Smart Images

Figure CN119185077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dental pulp capping materials, and in particular relates to an antibacterial composite hydrogel pulp capping agent for promoting dentin repair and a preparation method thereof. Background Art
[0002] Deep caries is one of the most common diseases that occur in teeth, often leading to infection and damage to the dental pulp. It is caused by cariogenic bacteria colonizing on the dentin and forming a biofilm, which damages the dentin that protects the dental pulp tissue and causes bacteria to invade the dental pulp, leading to pulp inflammation and necrosis. Pulp preservation is one of the important means of treating deep caries.
[0003] Pulp preservation is to use pulp capping materials to cover the dentin near the pulp or the exposed pulp tissue, promote the differentiation of pulp cells into odontoblasts, and thus form reparative dentin, which helps to protect the pulp tissue from external influences and provide a good hard tissue foundation for subsequent tooth restoration, so as to achieve the purpose of protecting the pulp and preserving the vitality of the tooth. Therefore, the performance of the pulp capping material is the key factor in determining the efficacy of pulp preservation, and the success of pulp preservation depends largely on whether the infection in the pulp can be completely eliminated, because bacterial contamination will have an adverse effect on the repair of the pulp-dentin complex.
[0004] Currently available bioactive pulp capping materials, such as calcium hydroxide and mineral trioxide aggregates, have been shown to have certain antibacterial properties and can promote odontoblastic differentiation of pulp cells and induce the formation of reparative hard tissue bridges. However, some studies have found that these pulp capping materials have limited antibacterial effects on certain microorganisms, which may lead to the failure of vital pulp preservation. Summary of the invention
[0005] In view of the above-mentioned prior art, the present invention provides an antibacterial composite hydrogel pulp capping agent for promoting dentin repair and a preparation method thereof, which solves the problem that pulp capping materials cannot simultaneously have anti-inflammatory and repair-promoting effects and long-term antibacterial effects.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an antibacterial composite hydrogel pulp capping agent that promotes dentin repair, comprising the following steps: S1: Mix rGO powder and AgNPs solution and ultrasonicate at 30-50KHz and 25℃ for 2-3h to obtain solution 1; S2: After the solution is evaporated and concentrated, it is centrifuged at a speed of 10000-15000 rpm for 15 min, and the lower precipitate is taken out and dried at 30°C for 24 h to obtain AgNPs-rGO powder; the AgNPs-rGO powder is redispersed in anhydrous ethanol to obtain AgNPs-rGO solution; S3: Mix GelMA and PBS, place in a dark water bath at 35-40°C and stir at 300-500 rpm for 1 h until completely dissolved to obtain a GelMA hydrogel precursor solution; S4: Mix DA and Tris-HCl solution, place in a light-proof water bath at room temperature and stir at 300-500 rpm for 30 min to obtain a polydopamine solution; S5: Mix the AgNPs-rGO solution, GelMA hydrogel precursor solution, polydopamine solution and Gap19 solution, and then stir at 300-500 rpm for 1 h in the dark to obtain AgNPs-rGO / PDA / GelMA@Gap19 dispersion; S6: The AgNPs-rGO / PDA / GelMA@Gap19 dispersion was irradiated with a 405 nm light source for 20-30 s to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
[0007] The beneficial effects of the present invention are as follows: in the present invention, AgNPs colloid and rGO powder are first mixed by ultrasound to obtain AgNPs-rGO. Under the action of multiple mechanisms such as physical destruction, reactive oxygen generation and enzyme inactivation caused by the synergistic effect of AgNPs and rGO, the composite material exhibits excellent performance in inhibiting and destroying the biofilm of Staphylococcus aureus, and can accelerate the healing of wounds infected by bacterial biofilms; the prepared AgNPs-rGO is then added to the GelMA hydrogel together with PDA and Gap19 to form the AgNPs-rGO / PDA / GelMA@Gap19 hydrogel (anti- GelMA has good physical and chemical properties and can be filled with inorganic nanoparticles to improve mechanical properties; Gap19, as a specific inhibitor of Cx43 hemichannels, can block its mediated hemichannel activity, reduce lipopolysaccharide (LPS)-induced inflammatory response of human dental pulp cells (hDPCs) by inhibiting the TLR4-NF-κB signaling pathway, and promote the odontoblastic differentiation of hDPCs under infection; the addition of PDA can be used as the main adhesive component; the preparation method is simple and easy, the prepared pulp capping material is easy to store, and is suitable for industrial production.
[0008] Based on the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the evaporation concentration process is to use a rotary evaporator at a rotation speed of 150 rpm and evaporate and concentrate in a 50° C. water bath for 2 to 3 hours.
[0010] Furthermore, the concentration of the AgNPs solution was 0.1 mg / mL, and the material-liquid ratio of rGO powder and AgNPs solution was 1 mg:2~3 mL.
[0011] The material-liquid ratio of rGO powder and AgNPs solution is 1 mg:2~3 mL.
[0012] Furthermore, the liquid ratio of GelMA and PBS was 0.8~1g:10mL.
[0013] Furthermore, the solid-liquid ratio of DA and Tris-HCl solution was 2 mg:1 mL.
[0014] Furthermore, the ratio of AgNPs-rGO solution, GelMA hydrogel precursor solution, polydopamine solution and Gap19 solution was 10~15:10:1:2~3.
[0015] The beneficial effect of adopting the further technical solution is that the product obtained by mixing the raw materials by utilizing a reasonable material-liquid ratio has a better effect.
[0016] The invention also discloses an antibacterial composite hydrogel pulp capping agent for promoting dentin repair prepared by the preparation method.
[0017] The beneficial effects of the present invention are as follows: the unique quantum size and surface effect of AgNPs give them strong penetration ability. They can fully destroy microbial membranes and have better antibacterial properties than traditional antibacterial agents. The presence of rGO can maintain the stable performance of AgNPs without agglomeration, so loading silver nanoparticles on rGO can help enhance their antibacterial properties. Gap19 is a polypeptide composed of 9 amino acids derived from the cytoplasmic loop (CL) of Cx43. It blocks intercellular exchange by inducing the degradation of Cx43 and is a specific inhibitor of Cx43 hemichannels. Cx43 is expressed in normal odontoblasts and during differentiation, but is abnormally expressed in caries lesions. Cx43 exchanges substances through gap junction channels and hemichannels. Normally, the hemichannels are in a closed state to prevent ATP loss and calcium ion influx, but under physiological conditions, they can be briefly opened to exert physiological functions. When the body is stimulated by related factors such as inflammation or changes in calcium ion concentration, the hemichannels may be over-opened, thereby promoting the development of the disease. Therefore, short-term hemichannel opening is normal, while uncontrolled opening may be harmful. Under physiological conditions, gap junctions mediated by Cx43 promote the differentiation and mineralization of dental pulp stem cells into odontoblasts by transferring calcium ions between adjacent cells, which may be related to the gap junction channel activity of Cx43; while under pathological conditions, inhibition of Cx43 hemichannels can attenuate the LPS-induced inflammatory response of hDPCs and promote their odontoblast differentiation. Therefore, Cx43 participates in and regulates the inflammatory and repair responses of dental pulp tissue, but it does not simply rely on changes in expression levels to play a role, but may function by forming hemichannels and gap junctions respectively. It can be seen that under infection, blocking Cx43 hemichannels can inhibit inflammation and promote tissue repair. Therefore, Gap19, as a specific inhibitor of Cx43 hemichannels, can inhibit the inflammatory response of the dental pulp without affecting the gap junction channels, thereby promoting its repair. PDA is an important natural melanin-like substance, which has attracted much attention due to its easy manufacture, good biodegradability, biocompatibility and adhesion. Therefore, the new pulp capping material of the present invention can inhibit pulp inflammation and promote its repair while being antibacterial. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 (a) is a 100 nm size TEM image of AgNPs-rGO powder in Example 1. Figure 1 (b) is a 50 nm size TEM image of AgNPs-rGO powder in Example 1. Figure 1 (c) is a 10 nm size TEM image of AgNPs-rGO powder in Example 1. Figure 1 (d) is the 5 nm size TEM image of AgNPs-rGO powder in Example 1; Figure 2It is a curve graph showing the effect of different concentrations of AgNPs-rGO on cell proliferation; Figure 3 The inhibition zone diagram of AgNPs-rGO filter paper with different concentrations on Staphylococcus aureus; Figure 4 It is the statistical diagram of the diameter of the inhibition zone; Figure 5 It is a curve graph showing the effect of different concentrations of Gap19 on cell proliferation; Figure 6 (a) is a 50 μm SEM image of the antibacterial composite hydrogel pulp capping agent for promoting dentin repair in Example 1. Figure 6 (b) is a 10 μm SEM image of the antibacterial composite hydrogel pulp capping agent for promoting dentin repair in Example 1. Figure 6 (c) is a 5 μm-sized SEM image of the antibacterial composite hydrogel pulp capping agent for promoting dentin repair in Example 1. Figure 6 (d) is a 1 μm size SEM image of the antibacterial composite hydrogel pulp capping agent for promoting dentin repair in Example 1; Figure 7 This is the EDS elemental analysis diagram of the antibacterial composite hydrogel pulp capping agent for promoting dentin repair prepared in Example 1; Figure 8 This is a typical image of the plate coating method to detect the number of surviving colonies after co-culture of the antibacterial dentin repair composite hydrogel pulp capping agent with bacteria; Fig. 9 The antibacterial rate of the composite hydrogel pulp capping agent for antibacterial dentin repair against Staphylococcus aureus; Fig.10 The antibacterial rate of the composite hydrogel pulp capping agent for antibacterial dentin repair against Escherichia coli; Fig.11 The antibacterial rate of mutans Streptococcus in composite hydrogel pulp capping agent for antibacterial dentin repair; Fig.12 The antibacterial rate of the composite hydrogel pulp capping agent for antibacterial dentin repair against lactobacilli; Fig.13 This is a graph showing the effect of the antibacterial composite hydrogel pulp capping agent on the ALP activity of osteoblasts; Fig.14 This is a statistical diagram showing the effect of the antibacterial composite hydrogel pulp capping agent on the ALP activity of osteoblasts. Fig.15 The effect of the composite hydrogel pulp capping agent for antibacterial and dentin repair on osteoblast matrix mineralization; Fig.16 Statistical chart of the effect of antibacterial composite hydrogel pulp capping agent on osteoblast matrix mineralization to promote dentin repair. DETAILED DESCRIPTION
[0019] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0020] Example 1 A method for preparing an antibacterial composite hydrogel pulp capping agent for promoting dentin repair comprises the following steps: S1: Mix rGO (reduced graphene oxide) powder and AgNPs (silver nanoparticles) solution with a concentration of 0.1 mg / mL at a solid-liquid ratio of 1 mg:2 mL, and ultrasonicate at 40 KHz and 25 °C for 2 h until the color of the mixed solution turns dark green to obtain solution 1; S2: The solution 1 was evaporated and concentrated using a rotary evaporator at a speed of 150 rpm in a 50°C water bath for 2.5 h, and then centrifuged at a speed of 12000 rpm for 15 min. The lower precipitate was taken and dried at 30°C for 24 h to obtain AgNPs-rGO powder; the AgNPs-rGO powder was redispersed in anhydrous ethanol to obtain an AgNPs-rGO solution; S3: GelMA (methacryloyl gelatin) and PBS were mixed at a solid-liquid ratio of 1 g:10 mL, placed in a light-proof water bath at 37°C and stirred at 400 rpm for 1 h until completely dissolved, to obtain a GelMA hydrogel precursor solution; S4: DA (dopamine) and Tris-HCl solution were mixed at a solid-liquid ratio of 2 mg:1 mL, placed in a light-proof water bath at room temperature and stirred at 400 rpm for 30 min to obtain a polydopamine solution; S5: AgNPs-rGO solution, GelMA hydrogel precursor solution, polydopamine solution and Gap19 solution were mixed in a ratio of 12:10:1:2.5, and then stirred at 400 rpm for 1 h in the dark to obtain AgNPs-rGO / PDA / GelMA@Gap19 dispersion; S6: The AgNPs-rGO / PDA / GelMA@Gap19 dispersion was irradiated with a 405 nm light source for 25 s to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
[0021] Example 2 S1: rGO (reduced graphene oxide) powder and AgNPs (silver nanoparticles) solution with a concentration of 0.1 mg / mL were mixed at a solid-liquid ratio of 1 mg:3 mL, and ultrasonicated at 30 KHz and 25 °C for 3 h until the color of the mixed solution turned dark green to obtain solution 1; S2: The solution 1 was evaporated and concentrated using a rotary evaporator at a speed of 150 rpm in a 50°C water bath for 2 h, and then centrifuged at a speed of 15000 rpm for 15 min. The lower precipitate was taken and dried at 30°C for 24 h to obtain AgNPs-rGO powder; the AgNPs-rGO powder was redispersed in anhydrous ethanol to obtain an AgNPs-rGO solution; S3: GelMA (methacryloyl gelatin) and PBS were mixed at a solid-liquid ratio of 0.8 g:10 mL, placed in a light-proof water bath at 35°C and stirred at 300 rpm for 1 h until completely dissolved to obtain a GelMA hydrogel precursor solution; S4: DA (dopamine) and Tris-HCl solution were mixed at a solid-liquid ratio of 2 mg:1 mL, placed in a light-proof water bath at room temperature and stirred at 300 rpm for 30 min to obtain a polydopamine solution; S5: AgNPs-rGO solution, GelMA hydrogel precursor solution, polydopamine solution and Gap19 solution were mixed in a ratio of 10:10:1:2, and then stirred at 300 rpm for 1 h in the dark to obtain AgNPs-rGO / PDA / GelMA@Gap19 dispersion; S6: The AgNPs-rGO / PDA / GelMA@Gap19 dispersion was irradiated with a 405 nm light source for 30 s to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
[0022] Example 3 S1: Mix rGO (reduced graphene oxide) powder and AgNPs (silver nanoparticles) solution with a concentration of 0.1 mg / mL at a solid-liquid ratio of 1 mg:2.5 mL, and ultrasonicate at 50 KHz and 25 °C for 2 h until the color of the mixed solution turns dark green to obtain solution 1; S2: The solution 1 was evaporated and concentrated using a rotary evaporator at a speed of 150 rpm in a 50°C water bath for 3 h, and then centrifuged at a speed of 10,000 rpm for 15 min. The lower precipitate was taken and dried at 30°C for 24 h to obtain AgNPs-rGO powder; the AgNPs-rGO powder was redispersed in anhydrous ethanol to obtain an AgNPs-rGO solution; S3: GelMA (methacryloyl gelatin) and PBS were mixed at a solid-liquid ratio of 0.9 g:10 mL, placed in a light-proof water bath at 40°C and stirred at 500 rpm for 1 h until completely dissolved, to obtain a GelMA hydrogel precursor solution; S4: DA (dopamine) and Tris-HCl solution were mixed at a solid-liquid ratio of 2 mg:1 mL, placed in a light-proof water bath at room temperature and stirred at 500 rpm for 30 min to obtain a polydopamine solution; S5: AgNPs-rGO solution, GelMA hydrogel precursor solution, polydopamine solution and Gap19 solution were mixed in a ratio of 15:10:1:3, and then stirred at 500 rpm for 1 h in the dark to obtain AgNPs-rGO / PDA / GelMA@Gap19 dispersion; S6: The AgNPs-rGO / PDA / GelMA@Gap19 dispersion was irradiated with a 405 nm light source for 20 s to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
[0023] The antibacterial composite hydrogel pulp capping agents for promoting dentin repair prepared in Examples 1 to 3 of the present invention have similar performance effects, and the antibacterial composite hydrogel pulp capping agent for promoting dentin repair prepared in Example 1 was used in subsequent experimental operations.
[0024] Comparative Example 1 A method for preparing an antibacterial composite hydrogel pulp capping agent for promoting dentin repair comprises the following steps: S1: Mix rGO (reduced graphene oxide) powder and AgNPs (silver nanoparticles) solution with a concentration of 0.1 mg / mL at a solid-liquid ratio of 1 mg:2 mL, and ultrasonicate at 40 KHz and 25 °C for 2 h until the color of the mixed solution turns dark green to obtain solution 1; S2: The solution 1 was evaporated and concentrated using a rotary evaporator at a speed of 150 rpm in a 50°C water bath for 2.5 h, and then centrifuged at a speed of 12000 rpm for 15 min. The lower precipitate was taken and dried at 30°C for 24 h to obtain AgNPs-rGO powder; the AgNPs-rGO powder was redispersed in anhydrous ethanol to obtain an AgNPs-rGO solution; S3: GelMA (methacryloyl gelatin) and PBS were mixed at a solid-liquid ratio of 1 g:10 mL, placed in a light-proof water bath at 37°C and stirred at 400 rpm for 1 h until completely dissolved, to obtain a GelMA hydrogel precursor solution; S4: DA (dopamine) and Tris-HCl solution were mixed at a solid-liquid ratio of 2 mg:1 mL, placed in a light-proof water bath at room temperature and stirred at 400 rpm for 30 min to obtain a polydopamine solution; S5: AgNPs-rGO solution, GelMA hydrogel precursor solution and polydopamine solution were mixed in a ratio of 12:10:1, and then stirred at 400 rpm for 1 h in the dark to obtain AgNPs-rGO / PDA / GelMA dispersion; S6: The AgNPs-rGO / PDA / GelMA dispersion was irradiated with a 405 nm light source for 25 s to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
[0025] Comparative Example 2 A method for preparing an antibacterial composite hydrogel pulp capping agent for promoting dentin repair comprises the following steps: S1: GelMA (methacryloyl gelatin) and PBS were mixed at a solid-liquid ratio of 1 g:10 mL, placed in a light-proof water bath at 37 °C and stirred at 400 rpm for 1 h until completely dissolved to obtain a GelMA hydrogel precursor solution; S2: DA (dopamine) and Tris-HCl solution were mixed at a solid-liquid ratio of 2 mg:1 mL, placed in a light-proof water bath at room temperature and stirred at 400 rpm for 30 min to obtain a polydopamine solution; S3: GelMA hydrogel precursor solution and polydopamine solution were mixed in a ratio of 10:1, and then stirred at 400 rpm for 1 h in the dark to obtain PDA / GelMA dispersion; S4: The PDA / GelMA dispersion was irradiated with a 405 nm light source for 25 seconds to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
[0026] Experimental Example 1 AgNPs-rGO characterization experiment: The AgNPs-rGO powder prepared in step S2 of Example 1 was examined using a transmission electron microscope, and the results are as follows: Figure 1 As shown, Figure 1 (a) TEM shows that rGO is wrinkled and its surface is decorated with dispersed AgNPs. Figure 1 (a)~(d) show that the particle size of the dispersed AgNPs is mostly about 10 nm, but there are also silver nanoparticles with larger particle sizes. The increase in their particle size indicates that it may help to enhance their antibacterial properties. This shows that AgNPs are successfully loaded onto rGO to form AgNPs-rGO.
[0027] Experimental Example 2 CCK-8 concentration experiment: The AgNPs-rGO powder prepared in step S2 of Example 1 was dispersed in anhydrous ethanol and diluted to different concentrations. The experiment was divided into 0.02 μg / mL AgNPs-rGO group, 0.1 μg / mL AgNPs-rGO group, 0.5 μg / mL AgNPs-rGO group, 2.5 μg / mL AgNPs-rGO group, 12.5 μg / mL AgNPs-rGO group, 62.5 μg / mL AgNPs-rGO group, 100 μg / mL AgNPs-rGO group, and control group (complete medium group), with 5 replicates in each group; hDPCs cells were cultured at 2×10 4Each well was inoculated in a 96-well plate and cultured for 24 hours. After the cells adhered to the wall, the culture medium was aspirated and 100 μL of the above culture medium was taken to culture hDPCs cells. At 24 hours, 48 hours, and 72 hours, the culture medium of each group was discarded, and the cells were washed twice with fresh α-MEM culture medium to remove the influence of drugs and materials. Then 100 μL of α-MEM and 10 μL of CCK-8 solution were added to each well, and the 96-well plate was placed in a cell culture incubator for 2 hours. The absorbance at a wavelength of 450 nm was measured with an enzyme marker to determine the optimal concentration for proliferation. The formula for calculating the relative proliferation rate (RGR) of cells is: RGR (%) = (OD value of the experimental group / OD value of the negative control group) �100%. The experimental results are shown in Figure 2 As shown in the figure, after 24 hours of culture, the addition of 12.5 μg / mL AgNPs-rGO had a more significant promoting effect on cell proliferation, and the relative cell proliferation rate was 140.20%; after 48 hours and 72 hours of culture, the cells in each group showed different degrees of reduction compared with the control group, among which the relative cell proliferation rates of the 12.5 μg / mL AgNPs-rGO group were 91.85% and 90.54%, respectively. According to the toxicity classification standard, the cytotoxicity of the 12.5 μg / mL AgNPs-rGO group was level 0, with no cytotoxicity.
[0028] Experimental Example 3 Inhibition zone experiment: The AgNPs-rGO powder prepared in step S2 of Example 1 was added to phosphate buffer solution (PBS) and diluted to different concentrations. The experiment was divided into 8 groups (3 samples in each group): control group (PBS group), 0.02μg / mL AgNPs-rGO group, 0.1μg / mL AgNPs-rGO group, 0.5μg / mL AgNPs-rGO group, 2.5μg / mL AgNPs-rGO group, 12.5μg / mL AgNPs-rGO group, 62.5μg / mL AgNPs-rGO group, 100μg / mL AgNPs-rGO group, and sterilized filter paper pieces with a diameter of 6 mm were placed in AgNPs-rGO of different concentrations for 24 hours. After 24 hours, the filter paper pieces were taken out and placed in the inoculated 1×10 6 CFU / mL Staphylococcus aureus on the surface of TSB solid culture medium, cultured in a bacterial incubator for 12 hours, and observed and recorded the size of the inhibition zone of each filter paper to determine the optimal antibacterial concentration. The experimental results are as follows Figure 3~4As shown in the figure, the antibacterial effect of different concentrations of AgNPs-rGO was determined by measuring the diameter of the inhibition zone between groups. No obvious inhibition zone was observed in the control group, 0.02μg / mL AgNPs-rGO group, 0.1μg / mL AgNPs-rGO group and 0.5μg / mL AgNPs-rGO group, while inhibition zones of different sizes were observed in the 100μg / mL AgNPs-rGO group, 62.5μg / mL AgNPs-rGO group, 12.5μg / mL AgNPs-rGO group and 2.5μg / mL AgNPs-rGO group, which were 10.43±0.48mm, 9.10±0.40mm, 8.27±0.23mm and 7.59±0.42mm, respectively.
[0029] Experimental Example 4 Gap19 concentration selection experiment: Gap19 was diluted into different concentrations using α-MEM complete medium (10% fetal bovine serum, 1% double antibody). The experiment was divided into 5 groups: control group (complete medium group), 2μM Gap19 group, 20μM Gap19 group, 200μM Gap19 group, and 400μM Gap19 group. After inoculating cells in the same way as in Experimental Example 2, the culture medium of each group was discarded at 24h, 48h, and 72h, and CCK-8 solution was added and incubated for 2h before measuring the absorbance at 450nm to determine the optimal concentration for proliferation. The experimental results are shown in Figure 2. Figure 5 As shown in the figure, by comparing the effects of different concentrations of Gap19 on cell proliferation, it was found that with the extension of culture time, under the action of 2μM and 20μM Gap19, the cells had obvious proliferation compared with the control group. Among them, the 20μM concentration of Gap19 had a more significant promoting effect on cell proliferation; while at high concentrations (200μM, 400μM), the number of cells was significantly reduced. The relative proliferation rates of the 20μM Gap19 group at 24h, 48h, and 72h were 105.84%, 119.51%, and 129.88%, respectively. According to the toxicity classification standard, the 20μM Gap19 group had a cytotoxicity of level 0, which was non-cytotoxic.
[0030] Experimental Example 5 Characterization experiment of the composite hydrogel pulp capping agent for promoting antibacterial dentin repair: The composite hydrogel pulp capping agent for promoting antibacterial dentin repair prepared in Example 1 was examined by scanning electron microscopy, and the results are as follows: Figure 6 As shown in the figure, it can be seen that the composite hydrogel is wrinkled and porous, and its three-dimensional network structure can provide a large specific surface area to load silver nanoparticles, which is beneficial to the diffusion of substances and the promotion of cell proliferation.
[0031] Experimental Example 6 EDS analysis: EDS element analysis was performed on the antibacterial dentin repair-promoting composite hydrogel pulp capping agent prepared in Example 1. The results are as follows: Figure 7 The main elements of the composite hydrogel pulp capping agent are C, O, N, and Ag, among which C, O, and N elements come from GelMA hydrogel, rGO, and Gap19, and Ag element comes from AgNPs. The antibacterial and dentin repair-promoting composite hydrogel pulp capping agent contains the constituent elements of AgNPs-rGO and Gap19, indicating that AgNPs-rGO and Gap19 are successfully loaded on the GelMA hydrogel.
[0032] Experimental Example 7 Antibacterial performance evaluation experiment: The experiment was divided into 5 groups (3 samples in each group): blank control group (GelMA hydrogel), MTA positive control group, PDA / GelMA hydrogel group (composite hydrogel pulp capping agent for antibacterial and dentin repair prepared in comparative example 2), AgNPs-rGO / PDA / GelMA hydrogel group (composite hydrogel pulp capping agent for antibacterial and dentin repair prepared in comparative example 1) and AgNPs-rGO / PDA / GelMA@Gap19 hydrogel group (composite hydrogel pulp capping agent for antibacterial and dentin repair prepared in example 1); the hydrogels in each group were made into discs with a diameter of 10 mm and a thickness of 2 mm. Staphylococcus aureus suspension, Escherichia coli suspension, Streptococcus mutans suspension, Lactobacillus suspension (1×10 6 CFU / mL) were added to the above 5 groups respectively, placed in a 37℃ constant temperature aerobic incubator (21% O2) / 37℃ anaerobic incubator (85% N2, 10% H2, 5% CO2) for co-culture for 24 hours, then 100μL of the bacterial solution in the co-culture solution was taken, diluted and spread on the solid culture medium, placed in a 37℃ constant temperature aerobic incubator (21% O2) / 37℃ anaerobic incubator (85% N2, 10% H2, 5% CO2) for 24 hours, and then the colonies on the solid culture dish were counted to determine the inhibition rate (R) of each group. The inhibition rate calculation formula is: R (%) = (the number of colonies in the blank control group - the number of colonies in the experimental group) / the number of colonies in the control group 100%. The experimental results are as follows Figures 8 to 12As shown in the figure, on the surface of the solid culture medium, compared with the control group, the CFU number of the AgNPs-rGO / PDA / GelMA group and the AgNPs-rGO / PDA / GelMA@Gap19 group was the least, followed by the MTA group. In addition, the CFU number of different types of bacteria showed a similar trend of change among the groups, indicating that the AgNPs-rGO / PDA / GelMA@Gap19 hydrogel has a certain broad-spectrum antibacterial effect. In order to more accurately evaluate the antibacterial properties of the composite hydrogel, the antibacterial rate was calculated by counting the number of bacterial CFU according to the antibacterial rate calculation formula. The antibacterial rates of the AgNPs-rGO / PDA / GelMA group and the AgNPs-rGO / PDA / GelMA@Gap19 group against Staphylococcus aureus were 89.74% and 90.14%, respectively; against Escherichia coli were 95.11% and 96.79%, respectively; against Streptococcus mutans were 98.55% and 99.05%, respectively; and against Lactobacillus were 99.78% and 99.85%, respectively, which were significantly higher than those of the control group and PDA / GelMA group (P<0.0001), and there was no significant difference in the antibacterial rates between the two groups (P>0.05). In addition, the MTA group also showed antibacterial activity against Staphylococcus aureus, Escherichia coli, Streptococcus mutans and Lactobacillus, which were 83.41%, 89.42%, 91.31% and 96.82%, respectively. Compared with the antibacterial rates of the AgNPs-rGO / PDA / GelMA group and the AgNPs-rGO / PDA / GelMA@Gap19 group against Staphylococcus aureus, Streptococcus mutans and Lactobacillus, there were significant differences (P<0.05), indicating that the AgNPs-rGO PDA / GelMA@Gap19 hydrogel has good antibacterial properties.
[0033] Experimental Example 8 ALP activity experiment: prepare α-MEM complete culture medium (containing 10% fetal bovine serum, 1% double antibody, 50 mg / L ascorbic acid, 10 mM sodium β-glycerophosphate, and 100 nmol / L dexamethasone).
[0034] The PDA / GelMA hydrogel group (the antibacterial and dentin repair-promoting composite hydrogel pulp capping agent prepared in Comparative Example 2), the AgNPs-rGO / PDA / GelMA hydrogel group (the antibacterial and dentin repair-promoting composite hydrogel pulp capping agent prepared in Comparative Example 1) and the AgNPs-rGO / PDA / GelMA@Gap19 hydrogel group (the antibacterial and dentin repair-promoting composite hydrogel pulp capping agent prepared in Example 1) were added with α-MEM complete culture medium, shaken at 37°C for 3 days, filtered and sterilized to obtain an extract.
[0035] The experiment was divided into 6 groups: blank control group (complete culture medium), 5 μg / mL LPS control group, MTA positive control group, PDA / GelMA extract group, AgNPs-rGO / PDA / GelMA extract group and AgNPs-rGO / PDA / GelMA@Gap19 extract group. hDPCs cells were cultured at 5×10 3 Each well was inoculated in a 6-well plate. Three samples were set up in each group. 1 mL of α-MEM complete medium was added to each well and cultured for 24 hours. After observing the cells adhered to the wall under a microscope, the culture medium was aspirated and discarded. The above 6 groups of culture medium were used to culture hDPCs cells respectively. The culture medium was changed every 2 days. After 7 days of culture, PBS was rinsed and fixed with 4% paraformaldehyde, and sterile PBS was washed 3 times. Then 1 mL of BCIP / NBT alkaline phosphatase colorimetric solution prepared strictly according to the instructions was added to each culture well for staining. The alkaline phosphatase staining of the sample was observed and recorded under a stereomicroscope. Another sample was taken after 7 days of culture, and the alkaline phosphatase (AKP) activity was detected using the AKP kit and the BCA kit. Samples were added and detected according to the instructions of the kit. The calculation formula of AKP activity is as follows: Cell AKP activity = {[(measured OD value-blank OD value) / (standard OD value-blank OD value)]*standard concentration (0.1 mg / ml)} / test sample protein concentration. The experimental results are shown in Figures 13 and 14 As shown in the figure, the alkaline phosphatase activities of the MTA group and the AgNPs-rGO / PDA / GelMA@Gap19 extract group were higher than those of the control group, and the activity of the AgNPs-rGO / PDA / GelMA@Gap19 extract group was the highest. The semi-quantitative results showed that compared with the control group, the alkaline phosphatase activities of the MTA group (P < 0.001) and the AgNPs-rGO / PDA / GelMA@Gap19 extract group (P < 0.001) were higher, and the alkaline phosphatase activity of the AgNPs-rGO / PDA / GelMA@Gap19 extract group was higher than that of the MTA group (P < 0.001), and the difference was statistically significant.
[0036] Experimental Example 9 Mineralization experiment: The experimental grouping was the same as that of Experimental Example 8. hDPCs cells were inoculated in a 6-well plate at 5×103 cells / well. Three samples were set up in each group. 1 mL of α-MEM complete medium was added to each well for 24 hours. After the cells were observed to adhere to the wall under a microscope, the medium was discarded and the above 6 groups of culture medium were used to culture hDPCs cells respectively. The culture medium was changed every 2 days. After 21 days of culture, the culture was terminated, fixed with 4% paraformaldehyde solution for 10 minutes, stained with Alizarin Red S solution at room temperature for 10 minutes, the staining solution was discarded, and the deionized water was repeatedly rinsed. The staining of the extracellular matrix mineralized nodules was observed and recorded under a stereo microscope. Semi-quantitative detection method of extracellular matrix mineralization: Cetylpyridinium chloride and 10mM sodium phosphate were mixed in a ratio of 1:9 to prepare an eluent, and its pH value was adjusted to 7.0. Next, 500 μL of the mixture was added to each well and shaken on a shaker for 30 min to wash away the stain from the sample surface. Subsequently, the OD value of each group of elution mixtures was measured at 620 nm using an ELISA reader. Figures 15 and 16 As shown in the figure, a small amount of red mineralized nodules were found in the LPS group, PDA / GelMA extract group, and AgNPs-rGO / PDA / GelMA extract group, a moderate amount of red mineralized nodules were found in the control group and MTA group, and a large amount of red mineralized nodules were found in the AgNPs-rGO / PDA / GelMA@Gap19 extract group. The semi-quantitative results showed that compared with the control group, the MTA group (P < 0.001) and the AgNPs-rGO / PDA / GelMA@Gap19 extract group (P < 0.001) had more calcified matrix, and the AgNPs-rGO / PDA / GelMA@Gap19 extract group had more than the MTA group (P < 0.001), and the difference was statistically significant.
[0037] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A method for preparing an antibacterial composite hydrogel pulp capping agent for promoting dentin repair, characterized in that: The following steps are involved: S1: Mix rGO powder and AgNPs solution and ultrasonicate at 30-50KHz and 25℃ for 2-3h to obtain solution 1; S2: After the solution is evaporated and concentrated, it is centrifuged at a speed of 10000-15000 rpm for 15 minutes, and the lower precipitate is taken out and dried at 30°C for 24 hours to obtain AgNPs-rGO powder; the AgNPs-rGO powder is redispersed in anhydrous ethanol to obtain an AgNPs-rGO solution; S3: Mix GelMA and PBS, place in a dark water bath at 35-40°C and stir at 300-500 rpm for 1 h until completely dissolved to obtain a GelMA hydrogel precursor solution; S4: Mix DA and Tris-HCl solution, place in a light-proof water bath at room temperature and stir at 300-500 rpm for 30 min to obtain a polydopamine solution; S5: Mix the AgNPs-rGO solution, GelMA hydrogel precursor solution, polydopamine solution and Gap19 solution, and then stir at 300-500 rpm for 1 h in the dark to obtain AgNPs-rGO / PDA / GelMA@Gap19 dispersion; S6: The AgNPs-rGO / PDA / GelMA@Gap19 dispersion was irradiated with a 405 nm light source for 20-30 s to obtain an antibacterial composite hydrogel pulp capping agent that promotes dentin repair.
2. The method for preparing the antibacterial composite hydrogel pulp capping agent for promoting dentin repair according to claim 1, characterized in that: The evaporation concentration process is to use a rotary evaporator at a rotation speed of 150 rpm and evaporate and concentrate for 2 to 3 hours in a 50° C. water bath.
3. The method for preparing the antibacterial composite hydrogel pulp capping agent for promoting dentin repair according to claim 1, characterized in that: The concentration of the AgNPs solution is 0.1 mg / mL, and the material-liquid ratio of the rGO powder and the AgNPs solution is 1 mg:2-3 mL.
4. The method for preparing the antibacterial composite hydrogel pulp capping agent for promoting dentin repair according to claim 1, characterized in that: The solid-liquid ratio of the GelMA and PBS is 0.8-1 g:10 mL.
5. The method for preparing the antibacterial composite hydrogel pulp capping agent for promoting dentin repair according to claim 1, characterized in that: The solid-liquid ratio of the DA and Tris-HCl solutions is 2 mg:1 mL.
6. The method for preparing the antibacterial composite hydrogel pulp capping agent for promoting dentin repair according to claim 1, characterized in that: The volume ratio of the AgNPs-rGO solution, the GelMA hydrogel precursor solution, the polydopamine solution and the Gap19 solution is 10-15:10:1:2-3.
7. The antibacterial composite hydrogel pulp capping agent for promoting dentin repair obtained by the preparation method according to any one of claims 1 to 6.
